The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/dom.12723
|View full text |Cite
|
Sign up to set email alerts
|

When β‐cells fail: lessons from dedifferentiation

Abstract: Diabetes is caused by a combination of impaired responsiveness to insulin and reduced production of insulin by the pancreas. Until recently, the decline of insulin production had been ascribed to β‐cell death. But recent research has shown that β‐cells do not die in diabetes, but undergo a silencing process, termed “dedifferentiation.” The main implication of this discovery is that β‐cells can be revived by appropriate treatments. We have shown that mitochondrial abnormalities are a key step in the progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
73
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 71 publications
6
73
0
2
Order By: Relevance
“…While increased β cell apoptosis may be responsible for the majority of decreased β cell mass in advanced T2DM patients (42,43), recently it has been suggested that an additional mechanism may exist. Thus, accumulation of dedifferentiated/ immature β cells, which express markers of both α and β cells, has been reported in mouse models of diabetes as well as in human T2DM islets (4,32,(43)(44)(45). While the origin of these dedifferentiated/immature β cells is still controversial in humans (32,43), it is plausible that strategies to suppress β cell apoptosis and/or increase β cell differentiation/maturation would be effective at improving β cell function.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While increased β cell apoptosis may be responsible for the majority of decreased β cell mass in advanced T2DM patients (42,43), recently it has been suggested that an additional mechanism may exist. Thus, accumulation of dedifferentiated/ immature β cells, which express markers of both α and β cells, has been reported in mouse models of diabetes as well as in human T2DM islets (4,32,(43)(44)(45). While the origin of these dedifferentiated/immature β cells is still controversial in humans (32,43), it is plausible that strategies to suppress β cell apoptosis and/or increase β cell differentiation/maturation would be effective at improving β cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, accumulation of dedifferentiated/ immature β cells, which express markers of both α and β cells, has been reported in mouse models of diabetes as well as in human T2DM islets (4,32,(43)(44)(45). While the origin of these dedifferentiated/immature β cells is still controversial in humans (32,43), it is plausible that strategies to suppress β cell apoptosis and/or increase β cell differentiation/maturation would be effective at improving β cell function. Interestingly, chronic FKN-Fc administration enhanced GSIS and decreased β cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to the latter feature, brilliant work has recently discovered "hubs" of b-cells that serve the function of synchronizing insulin discharge across the islet (74), a sort of specific conduction system analogous to that of the heart. The fundamental discovery of b-cell plasticity will add important details to the processes of dedifferentiation and redifferentiation of a-and b-cells (75)(76)(77)(78). By way of example, an antimalarial drug class, the artemisinins, facilitate transdifferentiation of a-to b-cells in a pathway involved in active GABA A receptor signaling in neurons (79).…”
Section: What Does the Future Hold?mentioning
confidence: 99%